Serum copeptin in women with gestational diabetes mellitus: A meta-analysis - Yuanqi He; Xue Li; Xiaoxiao Li; Weiwei Cui; Shihong Zhang (Biomolecules & Biomedicine, 2024)
To address inconsistencies in prior research, this meta-analysis examines the potential link between serum copeptin levels and the risk of developing gestational diabetes mellitus (GDM). Previous studies have reported mixed results regarding the relationship between serum copeptin levels and GDM risk. Our objective was to comprehensively evaluate this association. We systematically reviewed observational studies from Medline, Web of Science, Embase, Wanfang, and Chinese National Knowledge Infrastructure (CNKI) databases up to October 15, 2023, employing a random-effects model to integrate the data while considering heterogeneity. This analysis incorporated 10 studies comprising 625 women with GDM and 1212 healthy pregnant controls. Our findings showed no significant difference in serum copeptin levels between women with GDM and those without (standardized mean difference [SMD] 0.01, 95% confidence interval [CI] -0.22 to 0.24, P = 0.92, I2 = 75%). Univariate meta-analysis indicated a positive correlation between the body mass index (BMI) of the participants and the outcomes (coefficient = 0.11, P = 0.002). Further subgroup analysis demonstrated that women with a mean BMI ≥ 26 kg/m2 and GDM had significantly higher serum copeptin levels compared to their non-GDM counterparts (SMD 0.31, 95% CI 0.05 to 0.57, P = 0.02, I2 = 46%). Conversely, no difference was observed in women with a BMI < 26 kg/m2 (SMD -0.23, 95% CI -0.37 to -0.09, P = 0.002, I2 = 0%, P for subgroup difference = 0.003). Variables such as the country of study, maternal age, timing of blood sampling, copeptin measurement methods, or GDM diagnostic criteria did not significantly affect the results. In summary, the association between serum copeptin levels and GDM risk is influenced by the BMI of pregnant women, indicating that elevated serum copeptin might be linked to GDM in individuals with a BMI ≥ 26 kg/m2.